Financial stability and financial inclusion - Peter J. Morgan; Victor Pontines (Asian Development Bank Institute (ADBI), 2014)
Developing economies are seeking to promote financial inclusion, i.e., greater access to financial services for low-income households and firms, as part of their overall strategies for economic and financial development. This raises the question of whether financial stability and financial inclusion are, broadly speaking, substitutes or complements. In other words, does the move toward greater financial inclusion tend to increase or decrease financial stability? A number of studies have suggested both positive and negative ways in which financial inclusion could affect financial stability, but very few empirical studies have been made of their relationship. This partly reflects the scarcity and relative newness of data on financial inclusion. This study contributes to the literature on this subject by estimating the effects of various measures of financial inclusion (together with some control variables) on some measures of financial stability, including bank non-performing loans and bank Z-scores. We find some evidence that an increased share of lending to small and medium-sized enterprises (SMEs) aids financial stability, mainly by reducing non-performing loans (NPLs) and the probability of default by financial institutions. This suggests that policy measures to increase financial inclusion, at least by SMEs, would have the side-benefit of contributing to financial stability as well.
Keywords: G21; G28; O16; 330